Accountability affects the use of small group learning in school mathematics - Berry, John; Sahlberg, Pasi (NOMAD Nordic Studies in Mathematics Education, 2006)
This study investigates the perspectives of a sample of teachers on the use of cooperative small groups in the teaching and learning of mathematics. We asked teachers (N = 18) in England and Finland about their experiences and ideas of small group learning in mathematics. The research tool used the ordering by each teacher of eight mathematics tasks into a hierarchy from those tasks that are best for small group working to those tasks that are best for individual working as a frame for in-depth interviews. We conclude that the role of small group learning as seen by most of the teachers is for doing mathematics, introducing social skills and discussion rather than learning mathematical knowledge and skills. Furthermore we report on the barriers to using small group learning caused by the accountability structures inherent in the educational systems of both countries.